2021
DOI: 10.51680/ev.34.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z buying behavior change in the COVID-19 pandemic context

Abstract: Purpose: The purpose of this research is to analyze the changes in Croatian Generation Z buying behavior due to the COVID-19 pandemic. As a result of the pandemic, all governments have imposed different measures that directly and indirectly impact consumer behavior. Recent studies have mostly recorded a dynamic increase in online shopping, stockpiling, and change in priorities from luxury to basic goods. This study will specifically look into the relation between Generation Z buying behavior change and their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Moreover, pandemic-related studies on Gen Z examined their online shopping motives and buying behavioural change (Simic and Pap, 2021), purchasing/shopping behavioural shifts (Zwanka and Buff, 2021), information overload through social media (Liu et al, 2021), intent to use AR technology in shopping journey (Caboni and Pizzichini, 2022), etc. Since these nascent studies were conducted either at the beginning or ongoing phases of the pandemic, they are largely either exploratory or conceptual in nature.…”
mentioning
confidence: 99%
“…Moreover, pandemic-related studies on Gen Z examined their online shopping motives and buying behavioural change (Simic and Pap, 2021), purchasing/shopping behavioural shifts (Zwanka and Buff, 2021), information overload through social media (Liu et al, 2021), intent to use AR technology in shopping journey (Caboni and Pizzichini, 2022), etc. Since these nascent studies were conducted either at the beginning or ongoing phases of the pandemic, they are largely either exploratory or conceptual in nature.…”
mentioning
confidence: 99%
“…, 2016; Chareewan et al. , 2020; Hoxha and Zeqiraj, 2020; Leko Šimić and Pap, 2021; Barwińska-Małajowicz, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike Millennials, Gen Z is less aware of economic struggles. However, there is some evidence of their perception of decreased life quality due to COVID crisis (Bencsik et al, 2016;Chareewan et al, 2020;Hoxha and Zeqiraj, 2020;Leko Simi c and Pap, 2021;Barwi nska-Małajowicz, 2022).…”
Section: Generationsmentioning
confidence: 99%
“…Consumption levels fell by around 25% in some European countries (e.g. UK, Spain, Italy, and France) during the coronavirus crisis, while in the USA a 10% drop in consumption was recorded during this period [13]. Over the last 2 years, the COVID-19 pandemic has produced not only dramatic economic but also psychosocial effects, transforming many parameters of consumption behavior and more general lifestyle standards [14].…”
Section: Sociological Reflection On the Transformation Of Consumer Be...mentioning
confidence: 99%
“…Šimić and Pap [13] empirically observed changes in consumption behavior during the coronavirus crisis in Croatia within the Generation Z population, whose members are often referred to as "digital natives". Based on a quantitative data analysis conducted on a sample of 422 respondents, they showed that the consumption behavior of Generation Z during the coronavirus crisis led to much more stockpiling and overbuying.…”
Section: Sociological Reflection On the Transformation Of Consumer Be...mentioning
confidence: 99%